Characterisation of the flavin adenine dinucleotide binding region in Myxococcus xanthus protoporphyrinogen oxidase - Boateng, Mavis O (Department of Medicine, 2014)
This dissertation focuses on protoporphyrinogen oxidase (PPOX), the penultimate enzyme in the haem biosynthetic pathway. Partial defects in PPOX result in variegate porphyria, an autosomal dominant disorder. PPOX catalyzes the six electron oxidation of protoporphyrinogen IX to protoporphyrin IX, in the presence of flavin adenine dinucleotide (FAD) and oxygen. FAD is a cofactor, functioning as an intermediate electron acceptor in the catalytic function of PPOX. In this study the FAD binding region in Myxococcus xanthus PPOX was analysed by engineering and characterising a selection of relevant mutants.